Determination of features of composite steel and concrete slab behavior under fire condition - Nekora, Valeriia; Sidnei, Stanislav; Shnal, Taras; Nekora, Olga; Dankevych, Iryna; Pozdieiev, Serhii (Eastern-European Journal of Enterprise Technologies, 2021)
Methods for calculating the fire resistance of steel-reinforced concrete slabs made using profiled steel sheets under the influence of a standard temperature regime for more than 120 minutes are considered and analyzed. Research has been carried out to determine the heating parameters and the stress-strain state of steel-reinforced concrete slabs made using profiled steel sheets under fire conditions for more than 120 minutes. The results of this study allow to obtain indicators of temperature distribution for assessing the fire resistance of such structures for fire resistance classes above REI 120. Accordingly, the results obtained are a scientific basis for improving the existing method for calculating the fire resistance of steel-reinforced concrete slabs made using profiled steel sheets. The temperature distribution in the cross-section of structures was obtained using a general theoretical approach to solving the problem of heat conduction using the finite element method. Using the obtained temperature distributions, the parameters of the stress-strain state were determined based on the method of limiting states. To carry out the calculations, appropriate mathematical models were created that describe the effect of the standard temperature regime of a fire, to determine the temperature distribution at every minute in the sections of steel-reinforced concrete slabs with profiled steel sheets. A method is proposed for dividing the section into zones to take into account the decrease in the indicators of the mechanical properties of concrete and steel. A simplified method for the design assessment of steel-reinforced concrete slabs made using profiled steel sheets is proposed, which is consistent with the current EU standards and can be effectively used to analyze their fire resistance when establishing their compliance with the fire resistance class REI 120 and higher.